Effect of Cryopreservation Regimens on Behavior of SPEV Cells in Culture - Kovalenko, Igor F.; Kovalenko, Svetlana Ye.; Vysekantsev, Igor P.; Petrenko, Tatyana F.; Rozanov, Leonid F.; Chernobay, Nadezhda A. (Problems of Cryobiology and Cryomedicine, 2016)
This work demonstrates the ability of using the substrate-adhered SPEV cells as the object for studying the kinetics of osmotic reactions when exposing them to cryoprotective media. Permeability coefficients of SPEV cell membranes for the molecules of water and dimethyl sulfoxide (DMSO) have been determined. Using the physical-mathematical model for cell suspension freezing and calculated permeability coefficients the osmotic SPEV cell behavior during cryopreservation with different cooling rates has been simulated. The experiments on freezing the SPEV cell suspension showed that the cooling rate of 1.5 deg/min could ensure the optimal protection of the cells against damage in 1M DMSO presence. It has been demonstrated that the cooling rate above and below the optimum may cause a cell death as the result of intracellular crystallization or dehydration. Â  Probl Cryobiol Cryomed 2016; 26(2):116-123.